Improvement of Overall Equipment Efficiency of Machine by SMED. (2020) - Bhade, Suveg; Hegde, Sriharsha
Abstract: To stay in the competitive world, lead automobile companies must expand their production rate which is directly linked to the financial state of the organization. To improve the production rate as well as profit of any company is not a one-day process, but it requires some steps to achieve. Lean manufacturing has many tools to improve the production level of a machine. A lean tool like SMED can be used to improve the OEE of a machine. This tool is powerful when it comes to improve the global output of a machine. The aim of this study is to evaluate the stoppage losses of a machine and the effect of those in OEE of a machine, thereafter improving the OEE with Lean tools. Association of managerial and technical aspects is the main step taken to achieve the satisfactory result. An actual and experimental OEE is calculated and took possible corrective action to improve the rating of OEE. The result obtain is studied to reduce the productivity loss of an organization.